2012
DOI: 10.1021/om201177y
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivatable Organometallic Pyridyl Ruthenium(II) Arene Complexes

Abstract: The synthesis and characterization of a family of piano-stool Ru II arene complexes of the type [(η 6 -arene)Ru(N,N')(L)] [PF 6 ] 2 where arene is para-cymene (p-cym), hexamethylbenzene (hmb) or indane (ind); N,N' is 2,2'-bipyrimidine (bpm), 1,10-phenanthroline (phen), 1,10-phenanthroline-5,6-dione (phendio), 4,7-diphenyl-1,10-phenanthroline (bathophen), and L is pyridine (Py), 4-methylpyridine (4-MePy), 4-methoxypyridine (4-MeOPy), 4,4'-bipyridine (4,4'-biPy), 4-phenylpyridine (4-PhPy), 4-benzylpyridine (4-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 61 publications
5
114
0
Order By: Relevance
“…The UV-Vis absorption spectra of the complexes in dimethylsulfoxide ( Figure 1S and Table 1) were characterized by an intense high energy band centered at about 300 nm, which can be assigned to a ligand-localized, intra-ligand π-π* transition. Complexes 1-5 exhibited lower-energy bands in the range of 340-400 nm, which can be attributed as metal to ligand charge transfer (MLCT) transitions from Ru (dπ) to the ligand (π*) [28][29]. substituting the chloride atom [31].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The UV-Vis absorption spectra of the complexes in dimethylsulfoxide ( Figure 1S and Table 1) were characterized by an intense high energy band centered at about 300 nm, which can be assigned to a ligand-localized, intra-ligand π-π* transition. Complexes 1-5 exhibited lower-energy bands in the range of 340-400 nm, which can be attributed as metal to ligand charge transfer (MLCT) transitions from Ru (dπ) to the ligand (π*) [28][29]. substituting the chloride atom [31].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…In a recent study, Sokolov & Schaefer [93,94]. It has been shown that irradiated Ru-arene complexes bind to nucleobases such as 9-ethylguanine and to calf thymus DNA, whereas non-irradiated complexes bind negligibly.…”
Section: Photoactive Metal Complexes As Anti-cancer Agentsmentioning
confidence: 99%
“…A challenge for the TR-XSS technique is to extend its use to detect photoprocesses involving the release of multiatomic fragments formed by low-Z atoms such as, for example, C, N and O. For these reasons and for our interest in the photochemistry of Ru-diimine complexes [86,[230][231][232][233], we investigated, by TR-XSS, the ligand photodissociation reaction of the model compound cis-[Ru(bpy) 2 (py) 2 ]Cl 2 in aqueous solution (20 mm solution, ξ = 1.1 × 10 −4 ) [54]. This Ru-polypiridil derivative efficiently releases one pyridine ligand upon excitation of the metal-to-ligand charge-transfer (MLCT) band and subsequently coordinates a solvent molecule.…”
Section: (Py) 2 ] 2+mentioning
confidence: 99%